Desenvolvimento e avaliação de filmes antimicrobianos incorporados de alil isotiocianato e nanotubo de carbono na conservação de alimentos - Dias, Marali Vilela (2010)
The production of foods with quality and alimentary safety is a priority goal for the food industries. Besides good hygienic-sanitary practices, packaging in appropriate packages is also necessary to protect and to preserve the product. This work was carried out in two stages. First, the encapsulation of the allyl isothiocyanate (AIT) was studied and it was verified its adequacy in active packagings with and without nanocompounds, through the in vitro evaluation of those packagings regarding Salmonella Choleraesuis and Listeria innocua by volatilization and by direct contact. In the second stage, the developed films were applied on cooked, shredded chicken inoculated with Salmonella Choleraesuis, and evaluated through the reduction of the microbiological count, alterations in the color and oxidation characteristics and also the alterations in the mechanical and structural properties, and also the antimicrobial diffusion properties of the film to the food, during 40 days of storage. The results indicated that the development of films incorporated with AIT is possible, because they inhibited the growth of the studied microorganisms and their retention can be obtained with the encapsulation process with β-cyclodextrin and, or the use of carbon nanotubes (CNT). Considering the results of the application of the films on the chicken, the use of AIT is recommended at concentrations above 28%, combined with CNT concentrations over 0.02% to achieve microbiologial reduction, oxidation control and reduction in the color alterations, considering that those two factors did not influence the mechanical characteristics. Those packagings were efficient during 40 days of storage, because they allowed the diffusion of AIT to the chicken, representing a high application potential in food products.